2012
DOI: 10.1088/0022-3727/45/38/385301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EHD films by electrical capacitance

Abstract: The elastohydrodynamic (EHD) lubrication regime occurs in many machine elements where a combination of hydrodynamic effect, elastic deformation of the loaded surfaces and increase in the viscosity of the lubricant with pressure ensures the formation of a very thin, but continuous film of lubricant separating the contacting surfaces. Electrical methods to determine this film's thickness have preceded optical methods, which are widely used today. Although they generally give more qualitative thickness informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Also, as expected the capacitance falls with entrainment speed. Using the procedure explained in reference [17] for steel/steel contact, the film thickness was extracted from these capacitance values. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, as expected the capacitance falls with entrainment speed. Using the procedure explained in reference [17] for steel/steel contact, the film thickness was extracted from these capacitance values. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis carried out in [17] has also revealed that taking the extent of out -of -contact region up to a distance, from the contact centre, where the separation between surfaces is equal to nine times the central film thickness gives good approximation to calculated film thickness. Based on the glass/steel contact measurements Jablonka et al [17] have proposed a procedure for evaluation of film thickness, from capacitance, for steel/steel contacts.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Hamilton and Moore investigated this method already in 1974 [6]. Jablonka et al [8] used contact capacitance instead to measure the exact film thickness of an elasto-hydrodynamic contact in a ball on disc apparatus. Further, they did show that film thickness measurements by capacitance are influenced by the polarity of the lubricant [9].…”
Section: Introductionmentioning
confidence: 99%